The reconstruction of the Church of Ireland: Bishop Bramhall and the Laudian reforms, 1633-1641 - McCafferty, John (Cambridge University, 2013)
Thomas Wentworth landed in Ireland in 1633 - almost 100 years after Henry VIII had begun his break with Rome. The majority of the people were still Catholic. William Laud had just been elevated to Canterbury. A Yorkshire cleric, John Bramhall, followed the new viceroy and became, in less than one year, Bishop of Derry. This study, which is centred on Bramhall, examines how these three men embarked on a policy for the established church which not only represented a break with a century of reforming tradition but also sought to make the tiny Irish church a model for the other Stuart kingdoms. Dr McCafferty shows how accompanying canonical changes were explicitly implemented for notice and eventual adoption in England and Scotland. However, within eight years the experiment was blown apart and reconstruction denounced as subversive. Wentworth, Laud and Bramhall faced consequent disgrace, trial, death or exile.